The challenges of introduction of french language as a core subject in the new 9 year basic education curriculum structure (2010)
It is not an overstatement reiterating that French Language is an indispensable language in Nigeria and the world over, considering the numerical strength of the speakers of the language, its cosmopolitan status and because of its usefulness as an invaluable language of communication at different international forum such as United Nations summit, ECOWAS summit and African Union (AU) summit (French remains an indispensable language) in the recent time, the Nigerian Educational Research and Development Council (NERDC) announced its intention to elevate the status of French language from being a vocational elective subject to a core subject right from middle basic education curriculum to upper basic educational curriculum. The decision of the NERDC is a laudable and a welcome development considering the necessary invaluable status attached to the study of French language to boost international and diplomatic relations between Nigeria and her nieghbouring Francophone African countries (NPE2004). We are of the opinion that the programme with its beauty and laudability would face some challenges that would stand as a clog in the wheel of its successful realization. This paper therefore sets out to address the challenges of according a compulsory status to French language from primary four to Junior Secondary School in the new nine year basic curriculum structure.